Properties and Performance of Concrete Materials and Structures - Smarzewski, Piotr; Stolarski, Adam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue on "Properties and Performance of Concrete Materials and Structures" presents the current and relevant research and advances in the field of concrete composites, as well as covering a broad range of experimental studies in relation to high-performance, fiber-reinforced, self-compacting, and eco-efficient concrete materials and structures. Furthermore, analytical studies and numerical simulations are presented to show developments in the design methods of concrete composites. This Special Issue collects the most recent experimental techniques, analytical and numerical methods in relation to concrete materials and structures.